SPATIAL PANEL REGRESSION AND GEOGRAPHICALLY WEIGHTED PANEL REGRESSION MODELING OF DENGUE HEMORRHAGIC FEVER CASES IN WEST JAVA PROVINCE - Fatsa Vidyaningtyas Sabila; Yekti Widyaningsih (Diponegoro University, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus, transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. DHF case data containing spatial and temporal information is a form of spatial panel data that can be analyzed using spatial panel modeling. Spatial panel regression is a regression approach used to assess spatial autocorrelation in the data. Geographically Weighted Panel Regression (GWPR) is a local regression method capable of capturing spatial heterogeneity effects. This study aims to develop spatial panel regression and GWPR models to estimate the number of DHF cases and their associated factors at the regency/city level in West Java Province from 2021 to 2023. The results of the spatial panel lag regression model show that the number of hospitals and the percentage of households using safely managed sanitation services are statistically significant in explaining DHF cases. In contrast, the GWPR model with an adaptive bisquare kernel reveals variations in the local influence of variables. Significant variables in several regions include population density, number of hospitals, number of health centers, percentage of households with safely managed sanitation services, access to improved sanitation, poverty rate, and average number of elementary school students. Both models complement each other in the spatio-temporal analysis of DHF cases distribution.